Disturbance Identification and Adaptive Compensation Method in Optical Target Tracking System - Wenqiang Xia; Jiuqiang Deng; Kang Nie; Yao Mao; Xinglong Chen (IEEE Photonics Journal, 2024)
External disturbance suppression is critical in high-precision optical target tracking systems. Although the traditional disturbance observation compensator (DOBC) method can improve anti-disturbance performance, its fixed structure limits its ability to handle variable disturbances. To improve the suppression ability of time-varying narrowband disturbances, we propose a disturbance identification and adaptive compensation method based on DOBC (DIAC-DOBC). The peak frequency of the observed disturbance can be obtained with high precision using AR parameter model identification. To design the Q filter, an improved notch filter structure is proposed, with parameters that can be adjusted automatically and a stronger suppression ability. Furthermore, the conditions for closed-loop stability and robust stability are detailed. Finally, the method's effectiveness is demonstrated through simulation and actual experimentation on an optical target tracking system with disturbances.